Scattering of light waves by finite metal nanostrip gratings: Nystrom-Type method and resonance effects - Shapoval, O. V. (Radioelectronics and communications systems, 2015)
Efficient and rapidly convergent numerical algorithm for the simulation of the scattering of light waves by a finite gratings consisting of thin (thinner than the wavelength in the free space) metal nanostrips is presented. The model is based on the utilization of generalized boundary conditions (GBC), which allow one to exclude from consideration the field inside each strip and to reduce the two-dimensional boundary problem to one-dimensional systems of singular/hypersingular integral equations (IE). The obtained IE are solved numerically using the Nystrom-type method and the quadrature formulas of interpolation type, that provides guarantee convergence and controlled accuracy. The article presents the results of characteristics calculations for optical scattering and absorption by the gratings, which consist of silver nanostrips, as dependences on the width and on the thickness of the strips, and on the grating period. The nature of resonance phenomena has been investigated, namely the article presents the analysis of intensive optical scaterring and absorption in the case of excitation of plasmonic modes (plasmons) and of grating modes, which are induced by the periodicity.